Polycyclic aromatic hydrocarbons and development of respiratory and cardiovascular diseases in workers - Helenize Ferreira Lima Leachi; Maria Helena Palucci Marziale; Júlia Trevisan Martins; Patricia Aroni; Maria José Quina Galdino; Renata Perfeito Ribeiro
ABSTRACT Objectives: to identify the scientific evidence on the development of cardiovascular and respiratory diseases due to workplace contamination by polycyclic aromatic hydrocarbons. Methods: integrative literature review. The search for primary articles was held in October 2017 in the Medical Literature Analysis and Retrieval System Online (through Pubmed), Web of Science and Latin American and Caribbean Literature in Health Sciences (LILACS). Results: the 16 studies analyzed showed that exposure to polycyclic aromatic hydrocarbons was associated with cardiovascular diseases, such as increased blood pressure, heart rate variation, and ischemic heart disease; and respiratory disorders, such as decreased lung function, chronic obstructive pulmonary disease, asthma, wheeze, coughing, pulmonary wheezing, chest tightness, effort dyspnea, and sore throat. Conclusions: polycyclic aromatic hydrocarbons cause deleterious effects on the cardiovascular and respiratory systems through mutations and cellular inflammation, being a risk to exposed individuals.